The Influence Of The Implementation Of Good Governance And Internal Control On The Performance Of Urban Village Officials (Case Study In Pakuan Urban Village, South Bogor Sub-District) - Rosdiana, Anna; Indupurnahayu; Hurriyaturrohman (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2023)
This study aims to examine the influence of good governance, internal control on the performance of village officials. This research was conducted in the south Bogor sub-district with 60 Pakuan village officials as respondents. The result show that the effect of implementing good governance does not significantly affect the performance of village officials. Internal control has a significant positive effect on the performance of the village apparatus. This shows that the implementation of good governance is needed to improve the performance of the village apparatus